The Quality of Services Provided to Customers in zhe B2B Market with Chemical Industry Products - Vlčková, Vladimíra; Lošťáková, Hana (STEF92 Technology Ltd., 2017)
This paper specifies, on the basis of research outcomes and a primary survey, applied service quality indicators and service quality standards in the B2B market with selected chemical products. Finally, it specifies the importance of individual service quality parameters and the factors affecting it from the point of view of the service providers. The research was conducted using the method of personal interviewing of selected managers responsible for providing customer services at a selected chemical company. The benefits of the paper can particularly be seen in identification of the quality parameters of services that are important for customers in the chemical industry and that can significantly contribute to creation and maintenance of the customer satisfaction and loyalty in this market.
Kvalita služeb poskytovaných zákazníkům na B2B trhu s produkty chemického průmyslu
Keywords: customer services; quality of services; service quality indicators; chemical industry company; služby zákazníkům; kvalita služeb; ukazatelé kvality služeb; podnik chemického průmyslu